A descriptive audit of healthcare workers exposed to COVID‐19 at a tertiary care center in India. Issue 3 (18th April 2021) - Mansoor, Sadia; Sharma, K. Aparna; Ranjan, Piyush; Singhal, Seema; Meena, Jyoti; Kumari, Rajesh; Rana, Anubhuti; Kumari, Archana; Varun, Neha; Kumari, Sarita; Kumar, Sunesh; Bhatla, Neerja
Abstract: Objective: To provide a descriptive audit of healthcare workers (HCWs) exposed to COVID‐19, and their contacts, to understand the dynamics of transmission among HCWs. Methods: Retrospective analysis of contact tracing data of infected HCWs was done from March 1, 2020 to July 31, 2020 at a tertiary care center in New Delhi, India. Contacts were categorized according to the nature of contact and followed for 14 days. Results: Qualitative RT‐PCR testing was performed on 106 HCWs (from a total of 257) owing to exposure or development of symptoms. Positive results were found in 16 HCWs (6.2%) who were exposed to 120 other HCWs, generating 197 exposure incidents. Of these, 30 (15.2%) exposure incidents were high risk with multiple exposures in 48 (40.0%) HCWs. Exposure to infected HCWs was noted in 3 (18.8%) of 16 positive cases. Of the 197 exposure incidents, 54 (27.4%) were deemed avoidable exposures. Infection prevention and control policies were periodically reviewed, and the department implemented mitigating steps to minimize the risk to healthcare providers. Conclusion: Instituting appropriate infection prevention and control policies and use of adequate precautions by HCWs is vital to minimize high‐risk exposure to COVID‐19. Synopsis: COVID‐19 infection among healthcare workers can be avoided using appropriate on‐duty precautions to help provide sustained patient care during the current pandemic and beyond.